2004
DOI: 10.1021/mp0499196
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of P-Glycoprotein in Limiting Intestinal Absorption of Drugs:  Contribution of Passive Permeability to P-Glycoprotein Mediated Efflux Transport

Abstract: The aim of the present study is to evaluate the quantitative contribution of passive permeability to P-glycoprotein-mediated (P-gp-mediated) efflux and the functional activity of P-gp in determining intestinal absorption of drugs, and demonstrate the relationship between efflux parameters and intestinal permeability. MDRI-MDCKII cell monolayer permeability, human intestinal absorption (HIA), and solubility data were systematically collected from the literature. Drugs were classified as a total of 63 P-gp subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 27 publications
4
93
2
1
Order By: Relevance
“…The apparent molecular mass cutoff noted for BE may indicate that the potential substrate specificity of the transporters involved in hepatobiliary transport is associated with molecular mass. The fact that canalicular efflux transporters have a much wider substrate specificity implies that the secretion across canalicular membrane is not selective to a certain molecular size (Varma et al, 2005(Varma et al, , 2010aAller et al, 2009;Gandhi and Morris, 2009;Matsson et al, 2009). However, our analysis using a sizable dataset showed that hOATP and rOatp1b2 substrates tend toward large molecular mass ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The apparent molecular mass cutoff noted for BE may indicate that the potential substrate specificity of the transporters involved in hepatobiliary transport is associated with molecular mass. The fact that canalicular efflux transporters have a much wider substrate specificity implies that the secretion across canalicular membrane is not selective to a certain molecular size (Varma et al, 2005(Varma et al, , 2010aAller et al, 2009;Gandhi and Morris, 2009;Matsson et al, 2009). However, our analysis using a sizable dataset showed that hOATP and rOatp1b2 substrates tend toward large molecular mass ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Some of the compounds we have tested have been evaluated in conventional bidirectional transport studies. These studies showed that verapamil is a poorer P-gp substrate (efflux ratio of 1.7) than loperamide (efflux ratio of 9.9) (20,38). They also revealed that deprenyl and flumazenil are not P-gp substrates.…”
Section: Discussionmentioning
confidence: 97%
“…(therapeutic dose), the P-gp-mediated transport of sorafenib in patients might be saturated. Compared with digoxin, vinblastine (Table 2), and paclitaxel (efflux ratio of 108) (Varma et al, 2005), for which an in vivo effect of P-gp on the pharmacokinetics has been shown (Schinkel et al, 1994(Schinkel et al, , 1995van Asperen et al, 1998), sorafenib showed a lower efflux ratio in L-MDR1 cells. Summarizing the in vitro findings, with regard to its efflux ratio sorafenib is classified as a weak P-gp substrate.…”
Section: Discussionmentioning
confidence: 97%